2017
DOI: 10.1111/jir.12357
|View full text |Cite
|
Sign up to set email alerts
|

Aboriginal prisoners and cognitive impairment: the impact of dual disadvantage on Social and Emotional Wellbeing

Abstract: Culturally responsive disability assistance should be available at all phases of the justice system for Indigenous people with cognitive impairment to ensure that equitable care is accessible and needs are addressed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 41 publications
1
41
0
Order By: Relevance
“…Shepherd and colleagues found that participants with cognitive impairment were more likely to report having an illness or disability over the past 12 months, with "[a] diminished level of wellbeing for cognitively impaired Indigenous participants" (Shepherd et al 2017). In that study cognitive impairment was also found to be associated with:…”
Section: Impact Of Imprisonment On Indigenous Australians With Intellmentioning
confidence: 71%
See 4 more Smart Citations
“…Shepherd and colleagues found that participants with cognitive impairment were more likely to report having an illness or disability over the past 12 months, with "[a] diminished level of wellbeing for cognitively impaired Indigenous participants" (Shepherd et al 2017). In that study cognitive impairment was also found to be associated with:…”
Section: Impact Of Imprisonment On Indigenous Australians With Intellmentioning
confidence: 71%
“…It follows that the health and wellbeing of Indigenous prisoners with intellectual disability must be nested within this context. However, the specific needs of Indigenous people in custody with intellectual disability and cognitive impairments are not only poorly understood, but the importance of the social and emotional wellbeing of Aboriginal and Torres Strait Islander inmates with intellectual disability has purportedly not been given "any substantive consideration" (Shepherd et al 2017;Maxwell et al 2013).…”
Section: Impact Of Imprisonment On Indigenous Australians With Intellmentioning
confidence: 99%
See 3 more Smart Citations